Deforestation-focused policies do not reduce degradation in the Brazilian Amazon - Federico Cammelli; Holly K. Gibbs; Florian Gollnow; Samuel A. Levy; Matthieu Stigler; Rachael D. Garrett (Proceedings of the National Academy of Sciences, 2026)
Forest degradation causes large declines in carbon stocks, biodiversity, and ecosystem services, despite leaving some trees standing. Over the past two decades, numerous conservation policies to halt deforestation have been rolled out, but relatively little attention has been paid to tackling degradation. More information is needed to understand how deforestation and degradation are linked and how ongoing efforts to reduce deforestation are impacting degradation. With a focus on the case of the Brazilian Amazon, a place with highly dynamic deforestation, degradation, and policy conditions, we examine the effects of four types of deforestation policies on both deforestation and anthropogenic degradation. We find that with very few exceptions, both private supply chain policies and public deforestation policy mixes that successfully reduced deforestation failed to reduce anthropogenic forest degradation. This implies that deforestation control policies alone, which are the dominant approach to the conservation of forests, are insufficient to preserve biodiversity and carbon and safeguard forest-dependent livelihoods. Policy approaches that explicitly address fire, logging, fragmentation, and other degradation drivers are urgently needed to tackle these major gaps in current conservation policy approaches. Government and companies must also include forest degradation emissions in their evaluations of current policy effectiveness toward meeting emission reduction goals.